KAMPANYE CITRA KREATIF WILAYAH SELATAN MAKASSAR MELALUI TAGAR "#jamaahkreatifsektorselatan" DI MEDIA SOSIAL - Nurabdiansyah, Nurabdiansyah (Tanra: Jurnal Desain Komunikasi Visual Fakultas Seni Dan Desain Universitas Negeri Makassar, 2021)
Social media is now seen as one of the most important media to convey messages to the public. Messages from individuals and communities use this media as a space to share information and communicate with each other. Massive message delivery via social media, then followed by the trend of using hashtags to find out how many messages were sent and create identities. This study aims to examine the use of hashtags in a campaign about the creative community in Makassar entitled #jamaahkreatifsektorselatan (#JKSS). The #JKSS campaign is a creative effort to build the collective identity of several creative communities in the southern region of Makassar by inviting several communities that have several creative activities to add the hashtag #jamaahkreatifsektorselatan in each post on social media. This study then observed the use of #jamaahkreatifsektorselatan hashtags in social media and their correlation in building collective identities that could be used together. The main objective of this research is to examine the function and effectiveness of hashtags and social media in the creation of a community collective identity. Collective identity that can be used together then becomes a space to improve the social movements and the creative community development in Makassar.